Pengaruh Penambahan Konfirgurasi Foam Nine Cell Square Crash box terhadap Pola Deformasi dan Penyerapan Energi - Prayogo Arie Bowo; Kholis Nur Faizin (Infotekmesin, 2025)
Crash box is a crucial component in a vehicle's structure, designed to absorb impact energy. Crash box design has been developed to improve energy absorption capability. In this study, the square nine-cell crash box is varied with foam configuration. The addition of foam was chosen due to its lightweight as a filler for crash box. The research method used a computer simulation using ANSYS software. The nine-cell square crash box model consists of three squares, each with a length of 30 mm, 50 mm, and 65 mm, with a connecting rib thickness of 2 mm. Crash box performance is evaluated based on energy absorption and deformation patterns. Frontal load modeling on crash box was modeled with a speed of 12 m/s. Based on the simulation results, it can be found that the configuration of foam on the crash box affects the absorption energy and deformation patterns. The CF-CB 3 model provides energy absorption of 34% compared with no foam crash box due to a more uniform deformation pattern.